1987
DOI: 10.1002/tea.3660240307
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in national assessment of educational progress science items: What does “i don't know” really mean?

Abstract: The National Assessment of Educational Progress Science Assessment has consistently revealed small gender differences on science content items but not on science inquiry items. This assessment differs from others in that respondents can choose “I don't know” rather than guessing. This paper examines explanations for the gender differences including (a) differential prior instruction, (b) differential response to uncertainty and use of the “I don't know” response, (c) differential response to figurally presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 10 publications
0
17
1
Order By: Relevance
“…Linn and coworkers suggested that including the ''I don't know'' foil introduced risk-taking as a factor and that girls, in general, are more adverse to risk-taking than boys are. Further, gender differences in performance are exacerbated in multiple-choice tests by the ''I don't know'' foil, giving boys a 20% to 25% chance of receiving credit for a guess (Linn et al, 1987).…”
Section: Secondary Analyses Of Naep Science Assessmentsmentioning
confidence: 99%
“…Linn and coworkers suggested that including the ''I don't know'' foil introduced risk-taking as a factor and that girls, in general, are more adverse to risk-taking than boys are. Further, gender differences in performance are exacerbated in multiple-choice tests by the ''I don't know'' foil, giving boys a 20% to 25% chance of receiving credit for a guess (Linn et al, 1987).…”
Section: Secondary Analyses Of Naep Science Assessmentsmentioning
confidence: 99%
“…That is, multiple-choice tests reward students who guess (Rowley, 1974;Slakter, 1968), and boys are more willing to take this risk (Ben-Shakhar & Sinai, 1991;Hanna, 1986). Females, on the other hand, are more likely to choose an "I don't know" response option, particularly on physical science questions (Linn, Benedictis, Delucchi, Harris, & Stage, 1987). However, girls score significantly higher than boys on multiple-choice reading tests (Langer, Applebee, Mullis, & Foertsch, 1990;Pinnell et al, 1995), so it is not clear that format…”
mentioning
confidence: 95%
“…It can be said that males are more risk takers in performing on language tests. It has been suggested that girls are more reluctant to guess on multiple-choice questions than boys; boys overestimate their likelihood of success and hence take risks unknowingly, for which they are rewarded (Linn, et al 1987. Similarly, males tend to guess more on multiple-choice exams whereas girls tend to omit the items they are not sure about (Bolger and Kellaghan, 1990).…”
Section: Resultsmentioning
confidence: 93%